Bringing faith to the front : Catholic chaplains with the Second New Zealand Expeditionary Force, 1939-1945 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Buckley, Barry (Massey University, 2007)
Expeditionary Force (2NZEF) during World War Two has received relatively little recognition. Yet their presence began with the First Echelon that sailed to Egypt in January 1940 and remained an established part of the fighting forces in the Middle East, Europe and the Pacific until the end of the war. Their principal role was one of spiritual leadership and guidance and although unarmed non combatants, they shared the dangers of combat and were an important element in the treatment and care of casualties. Chaplains were acknowledged as being integral to the maintenance of morale. Many men needed assistance to cope with the violence and destruction and the military recognised that for many, a spiritual dimension was required which would provide assurance that there was some meaning behind it all. At the outbreak of war the suspicion with which the Protestant denominations and the Catholic Church had viewed one another had eased considerably and the beginnings of a much more cordial relationship were beginning to show. The military sought to have an ecumenical structure where denominational boundaries were minimised, with provision for separate Catholic liturgy. One of the successes of 2 NZEF was the manner in which Protestant and Catholic clergy worked co-operatively to provide a chaplaincy service that ministered to all yet preserved denominational integrity. Catholic chaplains had a different set of priorities than their Protestant colleagues. Their emphasis was to ensure that the sacraments were available to all Catholic soldiers and that no Catholic soldier would be disadvantaged by the failure to discharge that duty. Catholic teaching stressed that the way to God was through the reception of the sacraments and as such Catholic chaplains were constantly visiting their parishioners, who were scattered across the army, to say Mass, hear confessions and distribute communion. Consistent with the visiting was their attendance at battlefield stations to give fatally wounded Catholic men the last rites. While Catholic soldiers were their priority, in practice they provided support and comfort to whoever needed them, just as their Protestant colleagues did. For the Protestant denominations, religious worship in 2NZEF became more ecumenical over time. The Catholic chaplains had neither the inclination nor authority to embrace ecumenism and retained liturgical independence throughout the war. Yet the soldiers saw ecumenism practised in spirit, especially as the duties of Catholic and Protestant chaplains overlapped in an environment where co-operation was intrinsic to the success of the army and discord actively discouraged. In post war New Zealand the experiences of Catholic soldiers and their chaplains helped break down some of the artificial barriers between Catholic and Protestant and give some impetus to a slow ecumenical shift that would bear fruit some 20 years later.
Keywords: New Zealand; Military chaplains -- Catholic Church; New Zealand. Army. Expeditionary Force, 2nd -- Chaplains; World War, 1939-1945 -- Chaplains